Genetically diverse herpesviruses in South American Atlantic coast seabirds - Niemeyer, Claudia; Favero, Cíntia Maria; Shivaprasad, H.L.; Uhart, Marcela M.; Meyer Musso, Cesar; Rago, María Virginia; Silva-Filho, Rodolfo Pinho; Lima Canabarro, Paula; Craig, María Isabel; Olivera, Valeria Soledad; Pereda, Ariel Julian; Brandao, Paulo Eduardo; et al. (2017)
Different herpesviruses have been associated with respiratory and enteric disease and mortality among seabirds and waterfowl. In 2011, a respiratory disease outbreak affected 58.3% (98/168) of the Magellanic penguins undergoing rehabilitation due to an oil spill off the southern Brazilian coast. Etiology was attributed to a novel herpesvirus identified by histopathology, immunohistochemistry, electron microscopy and molecular studies with partial DNA sequencing. Since migration, rehabilitation and translocation may facilitate the spread of pathogens between populations and trigger the onset of clinical disease in animals with latent infections, investigation of herpesvirus occurrence in asymptomatic seabirds was performed. Samples from free-ranging seabirds were collected in Argentinian Patagonia (Magellanic penguins) and the Abrolhos Archipelago in Brazil (Brown boobies, Masked boobies, Red-billed tropicbirds, White-tailed tropicbirds and South American tern). Furthermore, asymptomatic seabirds housed at the facility where the outbreak occurred were also sampled. In total, 354 samples from eight seabird species were analyzed by PCR for herpesvirus. Four different sequences of herpesviruses were identified, one in Yellow-nosed Albatross, one in Boobies and Tropicbirds and two in Magellanic penguins. Magellanic penguin herpesvirus 1 was identified during the penguin outbreak at the rehabilitation facility in Brazil, while Magellanic penguin herpesvirus 2 was recovered from free-ranging penguins at four reproduction sites in Argentina. Phylogenic analysis of the herpesviruses sequences tentatively identified suggested that the one found in Suliformes and the one associated with the outbreak are related to sequences of viruses that have previously caused seabird die-offs. These findings reinforce the necessity for seabird disease surveillance programs overall, and particularly highlight the importance of quarantine, good hygiene, stress management and pre-release health exams in seabirds undergoing rehabilitation.